ASAS ULTIMUM REMEDIUM (THE LAST RESORT PRINCIPLE) TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DALAM RANGKA PERLINDUNGAN ANAK (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 125/PID/A/2012/PN.GS) - Beby Suryani Fithri; Muhammad Hamdan; Madiasa Ablisar; Jelly Leviza (Universitas Sumatera Utara, 2013)
The philosophy of juvenile justice system is to emphasize the rehabilitation of children in conflict with law as a person who has restrictions compared with adults. Children need the protection of the state and the society in the next period. It is necessary to seek a minimum intervention of the juvenile justice system against the children in conflict with law as a good strategy to protect them. The ultimum remedium/the last resort principle aims to protect the children in conflict with law in order to get their brighter future by keeping them away of the formal juvenile justice system and put it as the last choice to solve their cases. The ultimum remedium/the last resort principle is also useful to help the children in conflict with law by giving them warn and chance so that, they can find their identity and be the man in charge for themselves, their family, their society and their country. There will no presecution against the children in conflict with law and also they wont known as convict by applying the ultimum remedium/the last resort principle. It is why the juvenile judges need to really understand the principles of law and regulations relating to the disposal of the child so as to produce a wise judgment for the children in conflict with law.